Characterization of endolymphatic sac tumors and von Hippel–Lindau disease in the International Endolymphatic Sac Tumor Registry. (14th July 2015) - Bausch, Birke; Wellner, Ulrich; Peyre, Mathieu; Boedeker, Carsten C.; Hes, Frederik J.; Anglani, Mariagiulia; de Campos, Jose M.; Kanno, Hiroshi; Maher, Eamonn R.; Krauss, Tobias; Sansó, Gabriela; Barontini, Marta; et al.
Abstract: Background: Endolymphatic sac tumors (ELSTs) are, with a prevalence of up to 16%, a component of von Hippel–Lindau (VHL) disease. Data from international registries regarding heritable fraction and characteristics, germline VHL mutation frequency, and prevalence are lacking. Methods: Systematic registration of ELSTs from international centers of otorhinolaryngology and from multidisciplinary VHL centers' registries was performed. Molecular genetic analyses of the VHL gene were offered to all patients. Results: Our population‐based registry comprised 93 patients with ELST and 1789 patients with VHL. The prevalence of VHL germline mutations in apparently sporadic ELSTs was 39%. The prevalence of ELSTs in patients with VHL was 3.6%. ELST was the initial manifestation in 32% of patients with VHL‐ELST. Conclusion: Prevalence of ELST in VHL disease is much lower compared to the literature. VHL‐associated ELSTs can be the first presentation of the syndrome and mimic sporadic tumors, thus emphasizing the need of molecular testing in all presentations of ELST. © 2015 Wiley Periodicals, Inc. Head Neck 38: 673–679, 2016